Petrochemical catalyst materials, processes, and emerging technologies - Al-Megren, Hamid, 1962-; Xiao, Tiancun, 1965- (Advances in chemical and materials engineering (ACME) book series., 2016)
"This book addresses the latest research on emerging technological applications, catalyst materials for fuel upgrading, in addition to safety concerns and considerations within the petrochemical industry"--